Comparative Study of Software Technologies for Learning Science in Colleges of Education- Ghana - Asare, Isaac (International Journal of Scientific Research and Management (IJSRM), 2022)
Technology has now become integral part of our classrooms worldwide as one of the major means of delivering content to students. This study was to compare the use of some technology software for teaching and learning of science in the Colleges of Education in Ghana. It was conducted in six (6) Colleges of Education in the Central-Western zone. Questionnaire was used to collect data from the college students. The questionnaire consisted of seven (7) types of technology software which comprised of web-based software and non web-based software. Respondents responded according to their degree of acceptance of the use of each software for teaching and learning of science concepts. The findings were analysed using descriptive statistics. One hundred and twenty (120) teacher trainees were used for the study. The study showed that Social Media Platforms, E-mail, Google Classroom and WebQuest technology software were scarcely used for teaching and learning of science in the Colleges of Education in Ghana. It was however, indicated that Microsoft Excel, Microsoft Word and PowerPoint software were used often for teaching and learning of science.